TurtleUI: A Generic Graphical User Interface for Robot Control - Barros, Italo; Costa, Luis; Nascimento, Tiago (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
The development of robotic applications can become exhaustive as the complexity of work increases, and this problem comes with the need for multiple terminal tabs, terminal sessions and the need to often repeat multiple commands while running tests and experiments. This work presents a graphical interface developed through the PyQt framework, focused in robots equipped with Robot Operating System (ROS) framework and designed with the ease for starting processes, the ability to work with multiple terminals without leaving the application and reducing the need to perform basic commands repeatedly. The interface was validated with real robot experiments.